On Eryphus Perty, 1832 (Dichophyiini), Eriphus Audinet-Serville, 1834 (Trachyderini, Trachyderina), and Eryphus Klug, 1829, with description of a new genus, and corrections on publication dates (Coleoptera, Cerambycidae) - Antonio Santos-Silva; Juan Pablo Botero; Francisco Eriberto de Lima Nascimento (Papéis Avulsos de Zoologia, 2023)
Abstract The validity of two forgotten names, EryphusKlug, 1829 and E. rubricollisKlug, 1829, is discussed. The former is considered a nomen oblitum and synonymized with EriphusAudinet-Serville, 1834, a nomen protectum; the latter is revalidated and Eriphus purpuratus Chevrolat, 1862 is considered a junior synonym of Eriphus rubricollis (Klug, 1829). A lectotype is designated to Eryphus rubricollisKlug, 1829. The date of the work where EriphusAudinet-Serville, 1834 was described is corrected. A new genus is described in Dichophyiini Gistel, 1848 to include the species currently allocated in Eryphus sensuNapp & Martins (2002). The dates of publication of genera and species described by Fairmaire & Germain (Révision des Coléoptères du Chili (suite)) are corrected.